2004
DOI: 10.1038/sj.eye.6701642
|View full text |Cite
|
Sign up to set email alerts
|

Aniridia and optic nerve hypoplasia

Abstract: Background This study evaluates, in patients with aniridia, the prevalence of optic nerve hypoplasia and its association with foveal hypoplasia. Methods The medical records of 56 patients with aniridia (31 female, 25 male, mean age 33 years, range 2-74 years) were retrospectively evaluated for optic nerve and foveal hypoplasia. The difference in prevalence of foveal hypoplasia in patients with and without optic nerve hypoplasia was compared using Fisher's exact test. Results Six of 56 patients, 10.7% (95% CI: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 12 publications
1
21
2
1
Order By: Relevance
“…Although optic nerve hypoplasia has been reported in association with aniridia, 19 we did not find optic nerve hypoplasia or other types of optic disc anomalies. Moreover, we found no CNS malformation and mental retardation in our patients.…”
Section: Discussioncontrasting
confidence: 67%
“…Although optic nerve hypoplasia has been reported in association with aniridia, 19 we did not find optic nerve hypoplasia or other types of optic disc anomalies. Moreover, we found no CNS malformation and mental retardation in our patients.…”
Section: Discussioncontrasting
confidence: 67%
“…2,7 Optic nerve Optic nerve hypoplasia (small, malformed optic nerve) occurs in up to 10% of cases; optic nerve colobomata are also seen occasionally. 7,8 Refractive error, strabismus and ptosis Myopia, hypermetropia, astigmatism, as well as squints are commonly seen in aniridics. 5,7,11 Up to 10% of patients may have ptosis (drooping eyelid).…”
Section: Foveamentioning
confidence: 99%
“…Later onset cataracts, glaucoma and corneal opacification are responsible for progressive visual failure ( Figure 1). 1,2,[5][6][7][8][9] The phenotype can vary between and within families, but affected individuals usually show little difference between the two eyes. Most cases present within six weeks of birth with an obvious iris or pupillary abnormality or nystagmus.…”
Section: Introductionmentioning
confidence: 99%
“…This has introduced various terminologies such as fovea plana, foveal dysgenesis and foveal aplasia to describe the structural variability associated with arrested development of the fovea. [6][7][8] Mietz and colleagues suggested that foveal hypoplasia is a more appropriate terminology rather than aplasia since hypoplasia encompasses both the partial and complete absence of a structure. 9 Recent studies have shown that OCT can be used as a diagnostic aid and prognostic indicator for the foveal hypoplasia.…”
mentioning
confidence: 99%